TEACHER TALK: TEACHERS’ LANGUAGE AFFECTS STUDENTS’ CONFIDENCE - Gopporova Gulmira Shukhratbekovna (Modern American Journals, 2025)
This article highlights the role and importance of teacher's speech in forming students' self-confidence. The teacher's language, tone, attitude, and communication style in the lesson directly influence the psychological state, motivation, and learning process of students. Especially in English lessons, the teacher's encouraging and positive speech encourages students not to be afraid of mistakes, to express themselves freely, and to believe in their abilities. The study emphasizes that a teacher's positive language increases students' internal motivation to learn, creates an environment of psychological security during the lesson, and increases the effectiveness of language learning. Also, the teacher's cultural, emotional, and pedagogical competence in communication is assessed as an important factor in the personal development of students.
Keywords: Teacher's speech, self-confidence, motivation, communication culture, positive language, psychological environment, English language education, pedagogical competence.